Can prolife theorists justify an exception for rape? - Blackshaw, Bruce P. (Bioethics, 2022)
Prolife theorists typically hold to the claim that all human beings possess equal moral status from conception and consequently possess a right to life. This, they believe, entails that abortion is impermissible in all circumstances. Critics characterize this as an extreme anti-abortion position, as it prima facie allows no exceptions, even in cases of rape. Here, I examine whether the prolife claim regarding equal moral status is compatible with a more attractive moderate stance that permits an exception in the case of rape. I show that Judith Jarvis Thomson's analysis of rights can be used to modify the prolife position in this way, but that doing so involves concessions that prolife theorists are unlikely to find acceptable.